Short communication: Growth performance, nutrient digestibility and blood parameters of fattening lambs fed diet replacing corn with orange pulp - Lashkari, Saman; Taghizadeh, Akbar; Paya, Hamid; Jensen, Søren K. (Spanish Journal of Agricultural Research, 2017)
The objective of the present study was to evaluate the effect of replacing corn with orange pulp (OP) on growth performance, rumen fermentation, nutrient digestibility and blood parameters of fattening lambs. Twenty male lambs were placed in individual pens and fed with four levels of replacement of corn by OP (0, 33, 66, 100%) during 60 days. Average daily gain (ADG) showed a quadratic effect (p<0.007) with the increasing levels of replacement. Inclusion of 33 and 66% of OP in the diet significantly increased dry matter intake (DMI) compared to control group (p<0.01). Ruminal ammonia-N concentration showed a linear decrease (p<0.002). Ruminal fluid pH increased linearly with the increasing replacement of corn by OP (p<0.001). Acetate concentration showed a linear increase (p<0.001). Plasma total protein showed a linear increase (p<0.002). Organic matter, crude protein and neutral detergent fiber showed a quadratic effect with the level of replacement. The results of the present study showed that replacement of corn by OP improves DMI of fattening lambs, leading to an enhancement in ADG at the replacement level of 40.3%. Also, total replacement of corn by OP did not have any adverse effect on growth performance, rumen fermentation, nutrient digestibility and blood parameters.